Efektifitas aromaterapi peppermint terhadap mual muntah pada pasien kanker payudara yang menjalani kemoterapi - Sapti Ayubbana; Uswatun Hasanah (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
The effectiveness of peppermint aromatherapy on nausea and vomiting among breast cancer patients undergoing chemotherapyBackground: Breast cancer is a type of cancer and is one cause of death in the world. Chemotherapy is the use of chemical agents to control and destroy cancerous cells. Chemotherapy can induce nausea and vomiting, resulting in discomfort. One intervention that makes patients feel comfortable is giving peppermint aromatherapy.Purpose: To determine the effectiveness of peppermint aromatherapy on nausea and vomiting among breast cancer patients undergoing chemotherapy.Method: A quasi-experimental pretest-posttest group design, with a purposive sampling method of collecting samples. The study sample was 34 breast cancer patients who underwent chemotherapy. The sample divided into 2 groups as intervention & control groups. Measurement of nausea and vomiting used the Rhodes Index Nausea Vomiting & Retching (INVR) instrument.Results: Finding by the Man Whitney test, it showed that there was a difference in the scores for nausea and vomiting between the intervention group and the control group (p value = 0.008).Conclusion: Peppermint aromatherapy is effective in reducing nausea and vomiting among breast cancer patients undergoing chemotherapy.Keywords: Breast cancer; Chemotherapy, Nausea; Vomiting; Peppermint aromatherapyPendahuluan: Kanker payudara merupakan salah satu jenis kanker dan menjadi salah satu penyebab kematian di dunia. Kemoterapi merupakan penggunaan agen kimiawi untuk mengontrol dan menghancurkan sel yang bersifat kanker.Kemoterapi dapat menginduksi mual dan muntah mengakibatkan ketidaknyamanan. Salah satu intervensi yang membuat pasien merasa nyaman adalah dengan pemberian aromaterapi pepermint.Tujuan: Mengetahui efektifitas aromaterapi pepermint terhadap mual muntah pada pasien kanker payudara yang menjalani kemoterapi.Metode : Penelitian quasi experimental pretest-posttest group design, dengan metode pengumpulan sampel secara purposive sampling. Sampel penelitian sebanyak 34 pasien kanker payudara yang menjalani kemoterapi. Sampel terbagi atas dua kelompok; intervensi & kontrol. Pengukuran mual muntah menggunakan instrumen Rhodes Index Nausea Vomiting & Retching ( INVR).Hasil : Dengan menggunakan man whitney test menunjukkan bahwa terdapat perbedaan skor mual muntah antara kelompok intervensi dengan kelompok kontrol (p value = 0,008).Simpulan: Aromaterapi peppermint efektif menurunkan mual muntah pada pasien kanker kayudara yang menjalani kemoterapi.